PENYULUHAN HUKUM TENTANG PERATURAN POLRI NOMOR 8 TAHUN 2021 TENTANG PENANGANAN TINDAK PIDANA BERDASARKAN KEADILAN RESTORATIF - Rahman Amin; Gatot Efrianto; Octo Iskandar; Audy Pramudya Tama (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2023)
Changes in the paradigm of punishment fromretributive justice which is punitive or retaliatory to theperpetrators of criminal acts into a paradigm of restorativejustice or restorative justice is a settlement of cases that placesmore emphasis on aspects of recovery or improvement of theconsequences arising from the criminal acts that occurred, sothat it is expected to provide justice for all parties withoutreleasing the perpetrator's responsibility. To maximize theapplication of restorative justice in the handling of criminalcases, the Indonesia National Police have issued IndonesiaNational Police Regulation Number 8 of 2021 concerningHandling of Crimes Based on Restorative Justice, as a legal basisand guideline in resolving cases based on restorative justice.However, in reality, restorative justice still cannot beimplemented optimally, one of which is due to the lack ofknowledge and understanding of Indonesia National Polrimembers regarding the substance of Indonesia NationalRegulation Number 8 of 2021. The targets of this communityservice activity in the form of legal counseling are members ofthe Indonesia National Police serving at the Pasar Rebo SectorPolice, East Jakarta City Metro Police, and Regional PoliceMetro Jaya. The method of community service activities throughdirect legal counseling, which in its implementation consists ofthe preparation stage, the activity implementation stage, theevaluation stage, and the reporting stage. The results of thiscommunity service activity are, First, the implementation ofcommunity service activities in the form of legal counselingregarding Indonesia National Police Regulation Number 8 of2021 runs in an orderly and smooth manner from the beginningto the end of the activity without any significant obstacles andobstacles; Second, this community service activity has increasedthe knowledge and understanding of members of the Pasar ReboSector Police regarding the handling of criminal acts based onrestorative justice so that they can become provisions in carryingout their duties in the field.